Bilateral lateral rectus recession in exotropic Duane syndrome with downshoot - Gurung, Chandra Maya; Ganesh, Suma; Shrestha, Pawan (Nepalese Journal of Ophthalmology, 2016)
Objective: To report that maximum weakening of lateral rectus muscles can improve significant exotropia in primary position, abnormal head posture, retraction, narrowing of palpebral fissure and downshoot in exotropic duannes retraction syndrome. Case: A 12-year-old boy with exotropic Duane syndrome presented with downshoot and globe retraction in attempted adduction. Squint surgery was undertaken to correct the alignment and treat the secondary aberrant movements doing maximum weakening of the lateral rectus muscles by hang- back method. At 6 months follow up visit, there was improvement in abnormal head posture, reduction of ocular deviation with downshoot and stereoacuity. Conclusion: Supramaximal recession of lateral rectus muscles can correct exotropia with down shoot in a patient with Duane retraction syndrome. Nepal J Ophthalmol 2016; 8(15): 74-77